Functions of Macrophages in the Maintenance of Intestinal Homeostasis. (18th March 2019) - Wang, Shuai; Ye, Qianhong; Zeng, Xiangfang; Qiao, Shiyan
Abstract : Intestinal macrophages constitute the largest pool of macrophages in the body and have emerged as crucial sentinels for pathogen recognition and elimination. The source and development of intestinal macrophages, as well as their distinct properties have been well documented. Intestinal macrophages exert their functions in the maintenance of intestinal homeostasis by shaping host-microbiota symbiosis, managing gut inflammation, crosstalking with T cells, and facilitating wound repair. Recently, nutritional regulation of intestinal macrophages has attracted substantial attention and is becoming a promising approach to disease prevention and control. Understanding the mechanisms employed by intestinal macrophages in mediating intestinal immune homeostasis and inflammation, as well as the mode of action of dietary nutrients in the modulating functions of intestinal macrophages, represents an opportunity to prevent and control inflammatory bowel diseases.